Students’ psychological needs’ frustration in Physical Education and intention to be physically active from a person-centred approach - Alba González-Peño; Evelia Franco; Carmen Ocete; Javier Coterón (Psychology, Society & Education)
Although the benefits associated with physical activity have been evidenced, levels of physical activity among adolescents are still low. Physical Education classes seem to be the ideal context to promote the development of active lifestyles in students, so promoting their motivation will be fundamental. This study aims to establish profiles of Physical Education students according to their basic psychological need frustration and to explore the relationship between these profiles and the intention to be physically active depending on whether they practiced extracurricular physical activity. A total of 580 students participated, 413 of whom were engaged in out-of school physical activity, by completing a validated questionnaire. A cluster analysis was performed including the variables autonomy, competence, and relatedness frustration. The results showed the existence of three profiles (high, medium, and low frustration). Differences were found in the intention to be physically active as a function of extracurricular physical activity. Findings suggested that the detrimental role of basic psychological need frustration in Physical Education may be more evident among those students who already engage in physical activity.